2020
DOI: 10.3389/fpsyt.2020.555340
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Mismatch Negativity in Youth Affected by Autism Spectrum Disorder With and Without Attenuated Psychosis Syndrome

Abstract: The present study investigates the differences in auditory mismatch negativity (MMN) parameters given in a sample of young subjects with autism spectrum disorder (ASD, n = 37) with or without co-occurrent attenuated psychosis syndrome (APS). Our results show that ASD individuals present an MMN decreased amplitude and prolonged latency, without being influenced by concurrent APS. Additionally, when correlating the MMN indexes to clinical features, in the ASD + APS group, we found a negative correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…By contrast, in line with previous studies [ 41 , 42 , 43 ] we found a reduced MMN amplitude in the autistic population. However, no significant abnormalities emerged in the HIP group, which showed a mean MMN amplitude similar to that of NTD subjects.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…By contrast, in line with previous studies [ 41 , 42 , 43 ] we found a reduced MMN amplitude in the autistic population. However, no significant abnormalities emerged in the HIP group, which showed a mean MMN amplitude similar to that of NTD subjects.…”
Section: Discussionsupporting
confidence: 93%
“…ERPs represent a non-invasive method broadly investigated in neuropsychiatric research activities [ 34 ] to evaluate neurocognitive and attentive processes. Among ERPs, the mismatch negativity (MMN) and the P300 component have been widely explored in neurodevelopmental disorders [ 35 , 36 , 37 , 38 , 39 ] including autism [ 40 , 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing consensus that MMN is attenuated in autism compared to controls. The majority of studies have reported attenuated MMN amplitudes in children and adolescents with autism (Abdeltawwab & Baz, 2015; Di Lorenzo et al, 2020; Dunn et al, 2008; Huang et al, 2018; Lepisto et al, 2005; Lepisto et al, 2006; Ruiz‐Martinez et al, 2020; Vlaskamp et al, 2017), although a few studies found increased MMN amplitudes (Ferri et al, 2003; Lepisto et al, 2005; Yu et al, 2015) or no differences in MMN amplitudes (Chien et al, 2018; Gomot et al, 2011; Hudac et al, 2018; Jansson‐Verkasalo et al, 2003; Weismuller et al, 2015). However, a recent meta‐analysis (Chen et al, 2020) concluded that compared to controls, the MMN amplitudes in response to both speech‐sound and tone‐duration deviants are decreased in children but not adults with autism.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, results on whether the timing of the MMN peak differs in autism are inconsistent, as studies report both shorter MMN latencies (Gomot et al, 2002; Gomot et al, 2011; Vlaskamp et al, 2017), prolonged MNN latencies (Abdeltawwab & Baz, 2015; Di Lorenzo et al, 2020; Huang et al, 2018) and no difference in latencies (Yu et al, 2015) in children and adolescents with autism. Many studies have additionally explored if children with autism display abnormal brain potentials as sensory deviants enters awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is now widely used in clinical applications for the diagnosis of certain neurological deficits. Relevant studies have shown that compared with healthy children, patients with ASD have robust MMN deficits, thus suggesting an altered central ability in auditory discrimination ( Vlaskamp et al, 2017 ; Chen et al, 2020 ; Di Lorenzo et al, 2020 ). In the current study, a single-blind, sham-controlled experiment was designed for subjects with ASD.…”
Section: Introductionmentioning
confidence: 99%